REHABILITATION AGRICULTURE AREA COVERED BY SINABUNG VOLCANIC ASH - Agustoni Tarigan (Jurnal Pertanian Tropik, 2015)
The eruption of Mount Sinabung consistently and material issued increasingly large volume has caused plant and agricultural land damaged. Agricultural land damage was caused by the material issued mountain area is 10.945,24 ha. The role of technology and the results of research that has been done to agricultural lands caused the eruption of Mount Sinabung to be recommendations for the improvement of agricultural land. Efforts to improve the aspects of physical and chemical land are conservation, rehabilitation land of sand and the increase in the quality of the land. The thickness of volcanic ash after an eruption of covering agricultural land can be divided into 4 classes, namely: thin (the thickness < 2 cm), medium (thickness 2- 5 cm and thick (> 5 cm). Efforts for the recovery and rehabilitation land on each cluster based on the thickness of the dungeon ashes were normal processing with a hoe or plow, fertilizing with of organic matter and to the lava, dungeon needs to be done the conservation and land rehabilitation by an annual plant / the forest. The rehabilitation of agricultural land that badly damaged by eruption material may not be restored in a short time because of soil conditions which are acid, rocky and sandy. Thus the programs carried out by gradually and different treatment in accordance with their condition agricultural land.